Efficacy of integrative Traditional Chinese and Western medicine for the treatment of patients infected with 2019 novel coronavirus (COVID-19): A protocol for systematic review and meta analysis. Issue 29 (17th July 2020) - Liu, Dan; You, Yanyan; Chen, Yunhui; Tang, Songqi
Abstract: Background: No specific anti-virus drugs or vaccines have been available for the treatment of COVID-19. Integrative traditional Chinese and western medicine has been proposed as a therapeutic option with substantial applications in China. This protocol is proposed for a systematic review and meta-analysis that aims to evaluate the efficacy of integrative traditional Chinese and western medicine treatment on patients with COVID-19. Methods: Ten databases including PubMed, EMBASE, Cochrane Library, CIHAHL, Web of Science, Chinese National Knowledge Infrastructure (CNKI), Chinese Scientific Journals Database (VIP), Wanfang database, China Biomedical Literature Database (CBM) and Chinese Biomedical Literature Service System (SinoMed) will be searched. All published randomized controlled trials, clinical controlled trials, case-control, and case series that meet the pre-specified eligibility criteria will be included. Primary outcome measures include mortality, clinical recovery rate, duration of fever, progression rate from mild or moderate to severe, improvement of symptoms, biomarkers of laboratory examination and changes in computed tomography. Secondary outcomes include dosage of hormonotherapy, incidence and severity of adverse events and quality of life. Study selection, data extraction and assessment of bias risk will be conducted by 2 reviewers independently. RevMan software (V.5.3.5) will be used to perform data synthesis. Subgroup and sensitivity analysis will be performed when necessary. The strength of evidence will be assessed by the GRADE system. Results: This study will provide a well-reported and high-quality synthesis on the efficacy of integrative traditional Chinese and western medicine treatment on patients with COVID-19. Conclusion: This systematic review protocol will be helpful for providing evidence of whether integrative traditional Chinese and western medicine treatment is an effective therapeutic approach for patients with COVID-19. Ethics and dissemination: Ethical approval is unnecessary as no individual patient or privacy data is collected. The results of this study will be disseminated in a peer-reviewed scientific journal and/or conference presentation. Systematic review registration: PROSPERO CRD42020167205.